Die system design with finite element for improving mechanical performance of extruded aluminium alloys and composites - Al-Jaryawy, Hani Mizhir Magid (2015)
Aluminum extrusion is a forming process to produce a large variety of products with different and complex cross-sections. Understanding of the mechanics of aluminum extrusion process is still limited. It is necessary to improve the tools geometry in such a way that the extruded aluminum profile complies with high customer demands regarding to surface quality and dimensional accuracy. The extrudability of some aluminum alloys,specially the aluminum metal matrix composites (AMMCs) and their behavior and properties after extrusion process need to be improved. The objectives of this work are to improve the mechanical properties, accuracy and surface quality of aluminum extruded parts and composite extruded parts based on the selected parameter settings. Improvement was accomplished theoretically and experimentally through a completed series of steps, starting with designing all the required tools including group of die inserts with different geometrie and extrusion rates, followed by fabrication of all these inserts with a completed tool sets for experimental purposes. Finite element analysis and simulation method was utilized in this research to determine the optimum values of parameters before carrying out the experimental test. This ensures reducing the time for the trial and error, and gives more insight in the extrusion process and enhances the consistency of the results. The empirical part of this research includes a series of experimental tests for three types of alloys; aluminum alloy LM6, composite aluminum LM6/TiC, and aluminum alloy L168 as a hard alloy for comparison purpose. The aim is to assess the extrudability of composite alloy and their mechanical properties for each material after the process, and to identify the parameters that have a significant effect on mechanical properties. Experimental results show that, the product quality is dependent on the extrusion angle, die hardness, extrusion speed, temperature difference between tools and the billet, extrusion force and billet container length. The laboratory tests followed the experiments, like tensile and hardness tests, which gave indication of significant improvement of the mechanical properties after extrusion. Microstructure test, by Scanning Electron Microscope (SEM) and Energy Dispersive X- Ray Spectrometer (EDS) show a good improvement in parts micro-structures and grain size boundary layers after extrusion process. Both experimental and analytical results show a good indication of the possibility of extrusion of these alloys at different rates with good mechanical properties in both cold and hot extrusions. Moreover, one of the important contributions of this research is solving the sticking problem between the product with the die and container after extrusion, which leads to a high deformation during the product removal. This problem was studied and solved by design system which takes all these factors and variables into consideration.